Review on natural gums and mucilage and their application as excipient - Bahadur, Sanjib; Sahu, Uttam Kumar; Sahu, Dipesh; Sahu, Ghanshyam; Roy, Amit (Creative Pharma Assent, 2017)
Natural mucilage’s are included in novel drug delivered (NDDS) to multitask functions and in any cases directly or indirectly control the increase and rate of drug release. Substantial research efforts have been directed towards develop safe and efficient natural based mucilage particulate drug delivery systems., natural gums and mucilages and their isolation, purification, standardization and characterization characteristics along with their applications are covered. Recent trend towards the use of plant based and natural products demands the replacement of synthetic additives with natural ones. Today, the whole world is increasingly interested in natural drugs and excipients. These natural mucilages have advantages over synthetic ones since they are chemically inert, nontoxic, less expensive, and widely available.